Nucleophilic Substitution Reaction of Pyrimidin-2-yl Phosphates Using Amines and Thiols as Nucleophiles Mediated by PEG-400 as an Environmentally Friendly Solvent - Xing, Ting; Wei, Kai-Jie; Quan, Zheng-Jun; Wang, Xi-Cun (Synthesis, 2015)
A metal-free synthesis of C2-functionalized pyrimidines via the reaction of pyrimidin-2-yl phosphates with amines and thiophenols in PEG-400 has been developed. The desired products can be generated in good to excellent yields in the environmentally friendly PEG-400, without any catalysts or other additives.
Keywords: C2-functionalized pyrimidines; pyrimidin-2-yl phosphates; amines; thiophenols; cross-coupling; metal-free